2022
DOI: 10.1002/oby.23617
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood socioeconomic differences in BMI: The role of fast‐food outlets and physical activity facilities

Abstract: Objective: The goal of this study was to investigate the association between neighborhood socioeconomic status (NSES) and BMI and to what extent this association is moderated by availability of fast-food (FF) outlets and pay-for-use physical activity (PA) facilities.Methods: Baseline data of adults in Lifelines (N = 146,629) were linked to Statistics Netherlands and a register using geocoding to compute, respectively, NSES (i.e., low, middle, high) and the number of FF outlets and PA facilities within 1 km of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Diabetes, Metabolic Syndrome and Obesity 2023:16 4148 choose cheap and unhealthy foods, 26,27 leading to unhealthy dietary choices and lifestyles. The impact was particularly severe for both disproportionately affecting marginalized/disadvantaged populations.…”
Section: Dovepressmentioning
confidence: 99%
See 1 more Smart Citation
“…Diabetes, Metabolic Syndrome and Obesity 2023:16 4148 choose cheap and unhealthy foods, 26,27 leading to unhealthy dietary choices and lifestyles. The impact was particularly severe for both disproportionately affecting marginalized/disadvantaged populations.…”
Section: Dovepressmentioning
confidence: 99%
“…Studies had found that people living in areas with low socioeconomic indices had high rates of overweight or obesity, and that existing negative sociodemographic factors (unemployment, income insecurity, and education) seemed to have a cumulative effect. 25 They may face more economic pressures and restrictions and choose cheap and unhealthy foods, 26 , 27 leading to unhealthy dietary choices and lifestyles. The impact was particularly severe for both disproportionately affecting marginalized/disadvantaged populations.…”
Section: Severitymentioning
confidence: 99%